Use of plastic bags in street food and environmental degradation in Bonon (Central-western Côte d’Ivoire) - Eleazarus, Atsé Laudose Miguel (Geografares, 2026)
Street food vendors, who occupy public spaces in Bonon in an unregulated manner, use plastic bags, even though these are prohibited by the legal provisions in force in Côte d’Ivoire. The research aims to analyse the factors and environmental implications of the use of plastic bags in street food vending in the city. It involved semi-structured interviews with the authorities responsible for waste management, participatory observation and surveys of 100 vendors, 200 consumers and 160 households. The study showed that plastic bags are used excessively in street food vendors because they are easy to handle and accessible. However, poor management of plastic bags after use is a source of visual pollution, unsanitary conditions and degradation of the sanitation network, in a context of ignorance of legal provisions prohibiting the use of plastic bags and the inefficiency of the urban waste management system.
Keywords: Bonon; plastic bags; environmental degradation; street food